Small Claim Court Litigation Procedures And Mediation In State Court - Sanusi Sanusi; Kanti Rahayu; Tarno Ganang; Moh Taufik (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research was conducted with the aim of finding out how civil disputes are resolved in the District Court, either through Simple Lawsuits in Court or through Mediation in Court. By using normative juridical research methods, it is concluded: (1) The stages of simple lawsuit settlement in the District Court include registration, examination of the completeness of a simple lawsuit, determination of judges and appointment of substitute clerks, preliminary examination, determination of hearing days and summoning of parties, trial and peace hearings, evidence and decisions To resolve disputes in a simple and practical manner and avoid complicated settlements and in-depth examinations, Law Number 8 Year 1999 requires that amicable settlement, which is a legal remedy first attempted by the parties to the dispute, before the parties choose voluntarily to resolve disputes through the Judicial Body or other forum. (1) The Mediation Procedure in Article 13 on Submission of Case Resume and Duration of Mediation Procedure, states: (1) Within a maximum of 5 (five) working days after the parties have appointed an agreed mediator, each party may submit the case resume to each other and to the mediator. (2) Within a maximum of 5 (five) working days after the parties fail to select a mediator, each party may submit the case resume to the appointed mediator judge. (3) The mediation procedure shall last for a maximum of 40 (forty) working days from the time the mediator is selected by the parties or appointed by the chairman of the panel of judges as referred to in article 11 paragraphs (5) and ( 6). (4) Based on the agreement of the parties, the mediation period may be extended by a maximum of 14 (fourteen) working days from the expiry of the 40 (forty) day period as referred to in paragraph 3: (5) The period of the mediation procedure shall not include the period of case examination. (6) If necessary and based on the agreement of the parties, mediation may be conducted remotely using communication devices. Settlement of civil disputes in principle has two aspects, namely settlement through litigation and non-litigation, in the District Court itself where litigation settlement can be pursued also prioritizing the principles of fast, cheap, and simple.